Britain's economic prospects - Caves, Richard E. (Washington, D.C. : Brookings Institution; London : Allen & Unwin, 1968)
In this volume a team of American and Canadian economists analyzes the performance of the British economy and the effectiveness of Britain's economic policies.
Includes bibliographical footnotes and index.
rpm 25/01/2019
Loans
Keywords: Economic history; Economic policy; Great Britain